A Comparison of the Effectiveness of Emotion Regulation Training and Mindfulness Skills Training on Academic Burnout among Female Secondary School Students in Tehran - Yazdani Sarijeh , Fereshteh; Yousefi, Emad; Khajeh Pour , Leila (Mental Health and Lifestyle Journal, 2025)
This study aimed to compare the effectiveness of emotion regulation training and mindfulness skills training on reducing academic burnout in female secondary school students in Tehran. The research employed a quasi-experimental design with a pretest-posttest-follow-up structure and a control group. A total of 45 female students, selected through purposive sampling based on elevated aggression scores, were randomly assigned to three groups: emotion regulation training, mindfulness training, and control (15 participants each). The intervention programs were delivered over several sessions, with no intervention given to the control group. The Academic Burnout Questionnaire by Bresó et al. (1997) was used to measure outcomes across three time points: pretest, posttest, and one-month follow-up. The data were analyzed using repeated measures ANOVA and multivariate analysis of covariance with SPSS-24 to examine both within- and between-group differences. The results indicated significant reductions in academic burnout over time in both experimental groups compared to the control group. Multivariate analysis showed significant main effects for time (Wilks’ Lambda = 0.56, F(2,27) = 10.3, p < 0.001) and a significant interaction between time and group (Wilks’ Lambda = 0.70, F(2,27) = 5.62, p = 0.009). Univariate repeated measures analysis revealed that both emotion regulation and mindfulness training groups experienced significant reductions in academic burnout scores at posttest and follow-up. The mindfulness group demonstrated slightly greater and more stable effects across the measurement points. Both emotion regulation training and mindfulness skills training were effective in reducing academic burnout among female students, with mindfulness showing marginally superior outcomes. These interventions can serve as viable school-based strategies for addressing student burnout and promoting emotional resilience in academic settings.